2021
DOI: 10.3389/fnut.2021.644723
|View full text |Cite
|
Sign up to set email alerts
|

Current Landscape of Nutrition Within Prehabilitation Oncology Research: A Scoping Review

Abstract: Background: Prehabilitation aims to improve functional capacity prior to cancer treatment to achieve better psychosocial and clinical outcomes. Prehabilitation interventions vary considerably in design and delivery. In order to identify gaps in knowledge and facilitate the design of future studies, we undertook a scoping review of prehabilitation studies to map the range of work on prehabilitation being carried out in any cancer type and with a particular focus on diet or nutrition interventions.Objectives: Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 70 publications
(164 reference statements)
0
26
0
2
Order By: Relevance
“…Importantly, the NCPM provides a framework to guide professional nutrition practice. Given the recent scoping review of nutrition within prehabilitation research ( 7 ), which indicated that many nutrition interventions are currently conducted without reference to best practice guidelines, we suggest that implementation of the systematic NCPM could enhance the contribution of nutrition to prehabilitation and improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the NCPM provides a framework to guide professional nutrition practice. Given the recent scoping review of nutrition within prehabilitation research ( 7 ), which indicated that many nutrition interventions are currently conducted without reference to best practice guidelines, we suggest that implementation of the systematic NCPM could enhance the contribution of nutrition to prehabilitation and improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review of nutrition within prehabilitation oncology research identified that nutrition assessment was inconsistently applied across these studies, interventions did not often meet reference standards, and two-thirds of these studies did not monitor the nutrition intervention nor evaluate nutrition outcomes ( 7 ). Given that NCPM represents a global standard for provision of nutrition care, we advocate for its use in prehabilitation and have applied this model to the pre-operative surgical patient to illustrate how nutrition care can be effectively implemented and optimized.…”
Section: Nutrition Care Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Another multimodal approach implements a prehabilitation intervention that combines (1) personalized nutrition counseling and supplementation as needed, (2) individualized aerobic and weight resistance exercises, and (3) anxiety reduction and relaxation strategies to prepare patients for the anticipated detrimental effects of surgery. The majority of research has been conducted in surgery patients (94%), with several RCTs showing prehabilitation incorporating these three components facilitated earlier return to pre-surgery physical function levels and was associated with greater gains in muscle mass (compared to rehabilitation), and reduced hospital LOS and healthcare costs [61][62][63][64][65].…”
Section: Multidisciplinary Teams Provide Multimodal Treatmentmentioning
confidence: 99%